Determinants of the decision to use digital banking services of individual customers at Vietnamese commercial banks - Nguyen, Thi Thuy Huong; Nguyen, Van Lanh; Nguyen, Minh Nhat; Le, Thi Minh Ngoc; Truong, Quoc Cuong (Edelweiss Applied Science and Technology, 2025)
This paper investigates the key determinants influencing individual customers’ decisions to adopt digital banking services at Vietnamese commercial banks, focusing on factors such as perceived confidence, usefulness, financial cost, risk, trust, and bank brand image. Accordingly, the research employs a quantitative approach, utilizing multivariate regression and scale reliability testing via SPSS 26. Data were collected from 179 valid responses out of 250 online questionnaires distributed over four months (December 2024 to March 2025), targeting Vietnamese banking customers. The results indicate that perceived usefulness and confidence are the most significant drivers of digital banking adoption, while perceived financial cost and risk negatively impact the decision. In addition, trust and bank brand image also positively influence adoption, though to a lesser extent. The model explains 58.3% of the variance in adoption behavior. Moreover, perceived confidence and usefulness emerge as critical factors, underscoring the need for user-friendly and beneficial digital platforms, while cost and risk perceptions remain barriers despite recent fee reductions by banks. For practical implications, Vietnamese banks should enhance service usefulness, bolster customer confidence through education, and strengthen trust via robust security and branding strategies to accelerate digital banking adoption and support a cashless society transition.